Modelling small and medium-sized enterprises' failure in Malaysia - Abdullah, Nur Adiana Hiau; Ahmad, Abd Halim @ Hamilton; Zainudin, Nasruddin; Md Rus, Rohani (Inderscience Publishers, 2016)
Small and medium-sized enterprises (SMEs) are acknowledged as significant contributors to development and growth in the economy. Since failure among SMEs is common, this study intends to build an accurate model that could predict SME failure.An analysis on 132 companies in 2000 to 2010 shows that higher gearing and lower profitability are associated with higher failure risk.In addition, the incorporation of the company's age significantly improves the model's predictive accuracy.Our result indicates that young SMEs rely heavily on debt, which leads them into distressed situations.To validate the predictive accuracy of the model, the area under the receiver operating characteristic (ROC) curve is utilised, suggesting that the inclusion of the non-financial variable significantly improves the model.The overall prediction accuracy rate ranges from 75% to 89% for the model developed with non-financial variables when applied to the one-year, two-year, three-year and four-year prior-to-default holdout samples.